Análise experimental do deslocamento de líquidos em meios porosos artificiais por injeção de gás: efeito da capilaridade, inércia e diâmetro médio dos grãos - Silva, Ivanor Martins da (2012)
The displacement of a liquid in porous media by injecting another fluid is very applied in industrial processes such as oil recovery in a petroleum reservoir, cleaning of contaminated soils and geological sequestration of carbon dioxide (CO2). Currently the amount of oil that can be drawn from a reservoir varies between values below 20% to greater than 60% of the original volume of the reservoir (according [23] and [24]), due to the complexity of the process. With the continuous increase in oil prices in the market in recent decades, there is concern of humanity both to find new reserves and to increase the recovery factor of the existing ones. This presented work experimentally evaluates the fraction of lost mass or mass that is retained on an artificial porous medium consisting of artificial glass beads, when air is injected into the system to push a viscous liquid. Three solutions containing polyethylene glycol (PEG) are used as fluid displaced: a more concentrated PEG-water solution (more viscous fluid), a less concentrated PEG-water solution (less viscous fluid) and a solution of water and ethanol-PEG (fluid with low surface tension). We have investigated the influence of capillary number, which is the ratio between the viscous forces and the forces due to surface tension, and the diameter of the balls that make up the bed. The results are compared with the literature. Experiments are performed with four different porous media with an average diameter of 0.73 mm, 1.14 mm, 1.65 mm and 1.91 mm. It was concluded that the fraction of mass lost is not only function of dimensionless parameters such as Ca, but also dimensional quantities, such as surface tension, unlike the case in the capillary tube. Generally, the fraction of lost mass m increases with increasing Ca and with decreasing diameter of the spheres.